The Impact of Organizational Culture on Innovative Work Behavior Mediating Role of Perceived Organizational Support in Indonesian Small and Medium Enterprises (SMEs) - Khan, Muhammad Inzamam; Salendu, Alice; Azzahra, Fadia; Hussain, Shah (Utan Kayu Publishing, 2025)
This study examines how organizational culture influences innovative work behavior (IWB) in Indonesian small and medium enterprises (SMEs), focusing on the mediating role of perceived organizational support (POS). A survey of 296 SME employees, with 185 valid responses analyzed, shows that a culture emphasizing collaboration, adaptability, and employee empowerment significantly enhances innovation. However, POS does not mediate this relationship, indicating that cultural factors have a more direct impact. These findings highlight the need for SME managers to foster a workplace that encourages creativity, risk-taking, and knowledge-sharing to enhance innovation capacity. By embedding these cultural elements, SMEs can improve competitiveness despite resource constraints. The study contributes to the broader understanding of SME innovation in non-Western contexts, offering practical insights for leaders aiming to build innovation-driven organizations. Strengthening organizational culture can serve as a strategic approach to drive sustainable growth and resilience in the dynamic business landscape.